Solidification cracking during welding of steel: In situ X-ray observation. (May 2019) - Aucott, L.; Li, J.; Rack, A.; Dong, H. B.
Abstract: Solidification cracking is an important issue during welding, casting and some of the additive manufacturing process. In order to illuminate the failure mechanisms, solidification cracking during arc welding of steel are investigated in situ with high-speed, high energy, synchrotron X-ray radiography approach. Analysis of the in situ radiography sequence revealed the solidification cracking initiates in the weld sub-surface trailing the welding electrode at relatively low true strain of about 3.1% in the form of micro-cavities. Although both material type and bending speed influence solidification cracking, cracks propagate from the core of the weld towards the free surface along the solidifying grain boundaries was found at a speed of between 1.7 - 2.6 × 10 −3 m s −1 for three different steels. In addition, a three-stage mechanistic model for solidification cracking during welding of steel is proposed.